Development of New Canned Chub Mackerel Products Incorporating Edible Seaweeds—Influence on the Minerals and Trace Elements Composition - Vieira, Elsa F. (2020)
This study aimed to develop new canned chub mackerel products incorporating edible seaweeds (Ascophyllum nodosum, Fucus spiralis, Saccorhiza polyschides, Chondrus crispus, Porphyra sp. and Ulva sp.) harvested in the Portuguese North-Central coast, with simultaneous sensory improvement and minerals enrichment. Two processes were compared, namely the addition of seaweeds in i) the canning step and ii) in the brining step (as the replacement for salt). The concentrations of four macrominerals (Na, K, Ca and Mg), chloride, and twelve trace elements (Co, Cu, Fe, I, Li, Mn, Mo, Rb, Se, Sr, V and Zn) were determined by high-resolution continuum source flame atomic absorption spectrometry (HR-CS-FAAS) and inductively coupled plasma mass spectrometry (ICP-MS), respectively. Results showed that canned chub mackerel incorporating C. crispus and F. spiralis was found to be the preferred sensory option, also exhibiting contents enriched with Cl, Co, Cu, Fe, I, Li, Mg, Mn, Mo, Na, Rb, Se, and Sr. This effect was more pronounced when both seaweed species were added to replace the salt added in the brining step.